The book of Enoch the prophet - Charles, R. H. (Robert Henry), 1855-1931; Gilbert, R. A.; DuQuette, Lon Milo, 1948- (Weiser Books, 2012)
"Being a book wherein secret mysteries are revealed including the lost Books of Noah, the Prophesies of Enoch, particulars of Demonology and Angelology, and visions of the Apocalypse."--P. [4] of cover.